Desenvolvimento, caracterização físico-química e avaliação da solubilidade aquosa de cocristais de ácido ferúlico - Chaves Júnior, José Venâncio (2019)
The cocrystals are crystalline structures generated from the interaction of two or more substances in the same crystalline phase, which demonstrate the potential to improve technological and physicochemical parameters related to the pharmaceutical area, for example aqueous solubility which is a limiting factor on absorption of the drugs administered orally. The ferulic acid (FEA) is a molecule very studied for its antioxidant potential, in which its antitumor activities are highlighted, however the low aqueous solubility of this molecule appears as an obstacle to its clinical study. The objective of this work is to develop and characterize physicochemically cocrystals of FEA aiming to improve its aqueous solubility. The cocrystals were prepared by the drying technique under reduced pressure, using ethanol as solvent, and characterized by different analytical techniques: differential scanning calorimetry (DSC), X-ray powder diffraction (XRPD), Fourier transform infrared spectroscopy (FTIR), thermogravimetry (TG), nuclear magnetic resonance of hydrogen (NMR-¹H) and scanning electron microscopy (SEM), as well as an experimental planning was used and the in vitro dissolution evaluated. Among the coformers used, the nicotinamide (NIC) showed the best solubility results. The FEA and NIC cocrystal (CC) increase the solubility of FEA in 70% (1,33 mg/mL) compared to the FEA isolated (0,78 mg/mL). The methods for quantification of the FEA and NIC were developed and validated by high performance liquid chromatography (HPLC) and ultra high performance liquid chromatography (UHPLC). The process of obtaining CC showed good yield (98.3 ± 1.3%) and reproducibility. Analytical techniques provided strong evidence of cocrystal formation between the FEA and the NIC. The analytical techniques showed the formation of CC in the 1: 1 molar ratio, among the conditions used in the experimental planning. The CC showed better dissolution efficiency than the FEA alone in the media of pH 4.5 and 6.8. Considering the need for increasing the bioavailability of the FEA, the developed CC appears as a technological alternative for a more efficient pharmaceutical product for the FEA.